2003
DOI: 10.1177/1054137303256534
|View full text |Cite
|
Sign up to set email alerts
|

Coping with Death: Perceptions of Health Care Professionals Working in a Pediatric Intensive Care Unit and in a Geriatric Service

Abstract: Many health care professionals have to deal regularly with their patients' deaths and relatives' bereavement, but frequently they have not been trained in this area, and therefore the psychological cost is very high. The authors' principal aim in this work is to describe health care professionals' perceptions about death. A group of health care professionals who worked with children was compared with a group who worked with elderly people. Results showed that emotional aspects were perceived as more important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
0
8
0
3
Order By: Relevance
“…Furthermore, nurses' attitudes toward death may affect their empathy for patients [27], the quality of care [28], and the ways exploited to cope with the stress of patients' death [29]. In this regard, a study showed that nurses did not receive effective training to provide care for dying patients [25].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, nurses' attitudes toward death may affect their empathy for patients [27], the quality of care [28], and the ways exploited to cope with the stress of patients' death [29]. In this regard, a study showed that nurses did not receive effective training to provide care for dying patients [25].…”
Section: Discussionmentioning
confidence: 99%
“…El deterioro progresivo que implica el envejecimiento ha centrado el interés de estudios que analizan las actitudes que tiene la sociedad sobre las personas mayores y cómo éstas influyen en la imagen que los mayores tienen de sí mismos. De manera que éstos comparten una autoimagen de vejez negativa en la que prevalecen conceptos estereotipados como inutilidad, enfermedad, deterioro y carga para los demás (Arrieta y Espinosa, 2005; Shaw, Liang y Krause, 2010; Ulla et al, 2003). La imagen negativa que se origina en la persona mayor se relaciona con lo que Reig (2004) denomina "patrón cerrado a la vida", donde los hechos, los cambios y las dificultades son percibidos como amenazas, injusticias y pérdidas irreparables.…”
unclassified
“…Black (2007) suggested that health care professionals who demonstrate avoidant strategies such as ''fright, evasion, or dodging issues that involve death and dying'' are less likely to collaborate with other professionals (p. 569). A range of studies make similar recommendations: bereavement care coordination in acute hospitals (Bodenbach, 2005), peer support (Papadatou et al, 2002), assistance to sustain staff through multiple losses (Ferris et al, 1998;Holman, 2008), educational programs for hospital staff, particularly those with most direct contact with the dying and bereaved (Papadatou et al, 2001;Ferris et al, 1998;Tse et al, 2006;Ulla et al, 2003), and bereavement debriefing sessions, especially for less experienced 554 T. Walsh et al staff (Rushton et al, 2006). Generally, palliative and oncology healthcare professionals are of the view that contact should be made with bereaved relatives following death but that impediments to such practices existed such as time constraints, institutional factors, and personal barriers (Collins-Tracey et al, 2009).…”
Section: Literature Reviewmentioning
confidence: 88%
“…Many nurses and doctors lack confidence in dealing with the bereaved in a hospital setting (Tse et al, 2006). Healthcare professionals in both pediatric and geriatric services emphasize the importance of the emotional impact of dealing with death (Ulla et al, 2003). Black (2007) suggested that health care professionals who demonstrate avoidant strategies such as ''fright, evasion, or dodging issues that involve death and dying'' are less likely to collaborate with other professionals (p. 569).…”
Section: Literature Reviewmentioning
confidence: 99%